Exploring igneous rocks - Rogers, Marie, 1990- (New York : PowerKids Press, 2022)
Igneous rocks form when magma from Earth's core cools as it moves toward Earth's surface. Most of Earth is made of igneous rock, which is sometimes called "fire rock." In this text, readers learn the different kinds of igneous rock, how igneous rocks form, how igneous rocks fit into the rock cycle, and more.
Igneous rocks -- Molten rock -- Crystals -- Intrusive igneous rocks -- Extrusive igneous rocks -- Identifying a rock -- Cleavage and fracture -- Alteration -- Looking at history -- Rocks all around!
Includes index.
6.7
3-6
Keywords: Igneous rocks -- Juvenile literature; Igneous rocks